Eminence and Contributions of the Companions in the Development and Teaching of the Qur’anin the First Hijri Century - Norazman Alias; Nor Hafizi bin Yusof (School of Social Sciences & Humanities, University of Management and Technology (UMT), 2024)
Indexed by Scopus